Paeoniflorin improves functional recovery through repressing neuroinflammation and facilitating neurogenesis in rat stroke model - Tang, Hongli; Wu, Leiruo; Chen, Xixi; Li, Huiting; Huang, Baojun; Huang, Zhenyang; Zheng, Yiyang; Zhu, Liqing; Geng, Wujun (PeerJ (San Francisco, CA), 2021)
Microglia, neuron, and vascular cells constitute a dynamic functional neurovascular unit, which exerts the crucial role in functional recovery after ischemic stroke. Paeoniflorin, the principal active component of Paeoniae Radix, has been verified to exhibit neuroprotective roles in cerebralischemic injury. However, the mechanisms underlying the regulatory function of Paeoniflorin on neurovascular unit after cerebral ischemia are still unclear. In this study, adult male rats were treated with Paeoniflorin following transient middle cerebral artery occlusion (tMCAO), and then the functional behavioral tests (Foot-fault test and modified improved neurological function score, mNSS), microglial activation, neurogenesis and vasculogenesis were assessed. The current study showed that Paeoniflorin treatment exhibited a sensorimotor functional recovery as suggested via the Foot-fault test and the enhancement of spatial learning as suggested by the mNSS in rat stroke model. Paeoniflorin treatment repressed microglial cell proliferation and thus resulted in a significant decrease in proinflammatory cytokines IL-1 , IL-6 and TNF- . Compared with control, Paeoniflorin administration facilitated von Willebrand factor (an endothelia cell marker) and doublecortin (a neuroblasts marker) expression, indicating that Paeoniflorin contributed to neurogenesis and vasculogenesis in rat stroke model. Mechanistically, we verified that Paeoniflorin repressed JNK and NF- B signaling activation. These results demonstrate that Paeoniflorin represses neuroinflammation and facilitates neurogenesis in rat stroke model and might be a potential drug for the therapy of ischemic stroke.